Prospective association between standing balance and cognitive function in middle-aged and older Chinese adults - Yan, Jingzheng; Luan, Fangyun; Wang, Meijuan; Dong, Wenshuo; Zhang, Xinyue; Li, Mengli; Cao, Yingjuan (Frontiers in Psychology, 2022)
Objective To investigate the association of standing balance with cognitive functions and the rate of cognitive decline among middle-aged and older Chinese adults. Methods Participants were selected from China’s Health and Retirement Longitudinal Study. A total of 8,499 subjects aged ≥45 years who participated in wave 1 to wave 3 surveys were included in the final analysis. Standing balance was measured using the tandem test, and participants were categorized into two groups according to their ability to maintain standing balance. Cognitive functions were assessed in three domains: episodic memory, mental status, and global cognition. The associations between standing balance scores, cognitive scores, and the rate of cognitive decline were evaluated using linear regression and linear mixed models. Results Compared with participants who successfully completed the standing balance test, those who were unable to complete the test had lower scores on episodic memory [β = −0.18; 95% confidence interval (CI): −0.24, −0.11], mental status (β = −0.28; 95% CI: −0.37, −0.19), and global cognition (β = −0.51; 95% CI: −0.65, −0.38) after 4 years of follow-up. In addition, the rate of decline in mental status and global cognition increased by 0.10 (β = 0.10; 95% CI: 0.07, 0.13) and 0.08 (β = 0.08; 95% CI: 0.04, 0.12) units, respectively, in participants who were unable to complete the test compared with their counterparts. Conclusion Good standing balance was significantly associated with higher cognitive function and a lower decline in mental status and global cognition in middle-aged and older Chinese adults.